The conserved N-terminal region of Sendai virus nucleocapsid protein NP is required for nucleocapsid assembly. - Buchholz, C J (1993)
Sendai virus nucleocapsid protein NP synthesized in the absence of other viral components assembled into nucleocapsid-like particles. They were identical in density and morphology to authentic nucleocapsids but were smaller in size. The reduction in size was probably due to the fact that they contained RNA only 0.5 to 2 kb in length. Nucleocapsid assembly requires NP-NP and NP-RNA interactions. To identify domains on NP protein involved in nucleocapsid formation, 29 NP protein mutants were tested for the ability to assemble. Any deletion between amino acid residues 1 and 399 abolished formation of nucleocapsid-like particles, but mutants within this region exhibited two different phenotypes. Deletions between positions 83 and 384 completely abolished all interactions. Deletions between residues 1 and 82 and between residues 385 and 399, at the N- and C-terminal ends of the region from 1 to 399, resulted in unstructured aggregates of NP protein, indicating only a partial loss of function. Deletions within the C-terminal 124 amino acids were the only ones that did not affect assembly. The results suggest that NP protein can be divided into at least two separate domains which function independently of each other. Domain I (residues 1 to 399) seems to contain all of the structural information necessary for assembly, while domain II (residues 400 to 524) is not involved in nucleocapsid formation.